Location of the public service facilities in an urban comprehensive park using a multi-hierarchy and multi-constrained configuration model - Jie Yin; Bohao Su; Chenjing Fan; Qiuyuan Li (Journal of Urban Management, 2020)
The spatial layout of the public service facilities in urban comprehensive parks has to be optimized dynamically in accordance with user needs and local conditions. In this study, we present a multi-level hierarchical and multi-constrained model for locating public service facilities in an urban com-prehensive park. In this study, the service facilities of the park were classified into multiple levels based on the site selection of the facilities by integrating and processing current data with the use of ArcGIS. The different constraints for evaluating each level with respect to the construction quantity, accessibility, service area, and service object were also identified in this study. A traversal algorithm solution was used to obtain the corresponding optimal scheme in MATLAB. In the latter half of this study, Xuanwu Lake Park in Nanjing, China is presented as an example, the application of the model is introduced, and the model with the current situation of the park is compared with the traditional facilities configuration model. The planning and configuration model proposed in this study can be potentially used in the configuration of public service facilities in urban comprehensive parks in the future. This study provides a reference for the efficient operation and sustainable development of urban comprehensive parks.
Keywords: 710; Urban comprehensive park; Multi-hierarchy and multi-constrained configuration model; Public service facility